Pengembangan Bahan Ajar Teks Biografi Berbasis Nilai Etik di Era 4.0 - Suhariyanti Suhariyanti; Rani Rahim (Universitas Batanghari Jambi, 2022)
The development of teaching materials is part of the task of educators in teaching and learning activities. Teaching materials are very important for the continuity of effective teaching. Teaching materials are independent, meaning that a teacher can find, search, compile and develop teaching materials that suit the needs of students without going out on the standard path of content. Developing teaching materials can assist students in maximizing the performance of their learning outcomes. Efforts to develop teaching materials must be in accordance with a scientific/scientific approach and follow the times. We are currently in the industrial era 4.0 marked by the emergence of digital-based industries such as computers and mobile which have spread to all levels of society. But in reality the role of educators is getting new challenges in the 4.0 era. Based on the results of a literature study conducted by researchers, the cultivation of life values regarding good and bad has not been carried out optimally. It is proven from electronic media (television) and print media (newspapers) criminal cases between students, brawls between students, damaging the surrounding environment, promiscuity, pornography. Efforts to make it happen, researchers conducted observations at SMP IT Ibnu Khaldun. The results of the researchers' observations from interviews with teachers, students and analysis of textbooks, that teachers lack understanding in developing teaching materials, then students tend to focus on devices at home so that school assignments are ruled out and learning outcomes are less than optimal and the textbooks do not reflect values ethics in it. The purpose of this research is the process of developing biographical text teaching materials based on ethical values in the 4.0 era. And how is the feasibility of developing biographical text-based teaching materials based on ethical values in the 4.0 era. The teaching material developed is biographical text. The test used to measure student learning outcomes is a test to find the ethical values of biographical figures. The type of research used is R & D research using the development model of Thiagarajan, Semmel and Semmel, namely the 4-D Model. The teaching materials developed must be appropriate and effective and can improve student learning outcomes and increase ethical values in life.